Identifying Microbiome-Mediated Behaviour in Wild Vertebrates. (November 2020) - Davidson, Gabrielle L.; Raulo, Aura; Knowles, Sarah C.L.
Abstract : Recent research in laboratory animals has illuminated how the vertebrate gut microbiome can have diverse and powerful effects on the brain and behaviour. However, the ecological relevance of this microbiome–gut–brain (MGB) axis outside the laboratory remains unexplored. Here we argue that understanding behavioural and cognitive effects of the gut microbiome in natural populations is an important goal for behavioural ecology that may shed light on the mechanisms and evolution of behavioural plasticity. We outline a toolkit of approaches that could be applied in this endeavour and argue that beyond collecting observational data on the microbiome and behaviour from free-living animals, the incorporation of manipulative approaches tailored to such systems will be a key next step to progress understanding in this area. Highlights: Laboratory studies in model organisms have shown that the gut microbiome can strongly affect host behaviour and cognition through the microbiome–gut–brain (MGB) axis. However, the importance of such mechanisms in wild animals remains unknown. Associations of the gut microbiome with diet as well as with social interactions have been documented in wild animals. While these are usually interpreted to reflect the effect of host behaviour on the microbiome, effects in the opposite direction are also plausible. Measuring microbiota-mediated behavioural and cognitive plasticity in the wild will be necessary to identify the MGB axis's role in ecological and evolutionary processes.